2007
DOI: 10.1111/j.1440-1584.2007.00847.x
|View full text |Cite
|
Sign up to set email alerts
|

‘Shared Care – Shared Dream’: Model of shared care in rural Australia between mental health services and general practitioners

Abstract: This study offers a model on how a rural mental health service could enter into a shared care program with the local GP practice and achieve a greater level of satisfaction in serving the rural communities in Australia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 13 publications
0
6
0
Order By: Relevance
“…Effectiveness studies of collaborative care have included rural populations and some have primarily focused on rural populations . One Australian study focused on a shared care/collaborative care intervention in a rural clinic setting that worked to improve communication between general practitioners and psychiatric consultants . In child and adolescent psychiatry, where there are few trained specialists, consultation models and collaborative models that involve local primary care providers hold potential to leverage these skills .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Effectiveness studies of collaborative care have included rural populations and some have primarily focused on rural populations . One Australian study focused on a shared care/collaborative care intervention in a rural clinic setting that worked to improve communication between general practitioners and psychiatric consultants . In child and adolescent psychiatry, where there are few trained specialists, consultation models and collaborative models that involve local primary care providers hold potential to leverage these skills .…”
Section: Resultsmentioning
confidence: 99%
“…33,34 One Australian study focused on a shared care/collaborative care intervention in a rural clinic setting that worked to improve communication between general practitioners and psychiatric consultants. 35 In child and adolescent psychiatry, where there are few trained specialists, consultation models and collaborative models that involve local primary care providers hold potential to leverage these skills. 36 Finally, the Improving Access to Psychological Therapies (IAPT) initiative in primary care clinics in England, while not focused on collaborative care, has dedicated considerable funds to train therapists in cognitive behavioral therapy who offer stepped care for depression and anxiety in primary care.…”
Section: Other Providers In Primary Care and Specialist Supportmentioning
confidence: 99%
“…While the concept of primary and specialist shared care models is not novel, [20][21][22] only one published Australian report was found that had explored their effectiveness for patients treated with clozapine. 17 To assist in providing guidance to other services establishing similar care pathways, the results of the current study may facilitate the selection of suitable patients for transitioning, based on the characteristics in Figure 4 that distinguished transitioned patients from those remaining in PMHS care.…”
Section: Discussionmentioning
confidence: 99%
“…A potential way to address this issue is to consider shared‐care models. Shared‐care provides single point integrated services, which maximise access to quality locally available care, provides mutual professional support and reduced travel 45,46 and has shown to be positively received by cancer patients 47 and beneficial in rural settings 48 . With increasingly widespread telehealth capabilities, the ability for patients and clinicians from both the rural and tertiary services to connect for online consultation and to deliver coordinated and collaborative shared‐care is a potential solution.…”
Section: Discussionmentioning
confidence: 99%